Microplastics in agriculture – a potential novel mechanism for the delivery of human pathogens onto crops - Quilliam, Richard S.; Pow, Chloe J.; Shilla, Dativa J.; Mwesiga, James J.; Shilla, Daniel A.; Woodford, Luke (Frontiers in Plant Science, 2023)
Mulching with plastic sheeting, the use of plastic carriers in seed coatings, and irrigation with wastewater or contaminated surface water have resulted in plastics, and microplastics, becoming ubiquitous in agricultural soils. Once in the environment, plastic surfaces quickly become colonised by microbial biofilm comprised of a diverse microbial community. This socalled 'plastisphere' community can also include human pathogens, particularly if the plastic has been exposed to faecal contamination (e.g., from wastewater or organic manures and livestock faeces). The plastisphere is hypothesised to facilitate the survival and dissemination of pathogens, and therefore plastics in agricultural systems could play a significant role in transferring human pathogens to crops, particularly as microplastics adhering to ready to eat crops are difficult to remove by washing. In this paper we critically discuss the pathways for human pathogens associated with microplastics to interact with crop leaves and roots, and the potential for the transfer, adherence, and uptake of human pathogens from the plastisphere to plants. Globally, the concentration of plastics in agricultural soils are increasing, therefore, quantifying the potential for the plastisphere to transfer human pathogens into the food chain needs to be treated as a priority.